Genetic divergence in pumpkin (Cucurbita moschata L.) Genotypes (Bangladesh Journal of Agricultural Research, 2016)
Genetic diversity using Mahalanobiss D2 technique was studied for yield and its components on twenty one genotypes of pumpkin (Cucurbita moschata L.). Quantification of variability for each character was done using the Shannon Weaver Diversity Index. High degree of variation was exhibited within the collection, as reflected by mean diversity index value of 0.80. Data were subjected to principal component analysis (PCA), principal coordinate analysis (PCO), canonical variate analysis (CVA) and non-hierarchical clustering to identify suitable parents having distant relationship for hybridization program. The genotypes were grouped into five different clusters. Cluster IV contained the maximum number of seven genotypes whereas cluster I contained least number having only one genotype. The lowest inter-genotypic distance (0.75) was found between BD-2174 and BD-9489 where the highest (47.46) was between BARI Mistikumra-1 and BD-2150. The maximum inter cluster distance was observed between cluster II and III (17.922) and the minimum inter cluster distance was observed between cluster II and IV (6.825). The maximum intra cluster distance was noticed for the cluster V (0.261) and the minimum intra cluster distance was found in cluster I (0.00). Cluster I contained the highest mean values for pedicel length of male flower, number of male flowers/plant, fruit length, fruit breadth, single fruit weight and fruits/plant. Cluster II contained the highest mean values for days to first male and female flowering. Cluster III contained the highest mean values for leaf breadth, pedicel length of female flower and number of female flowers/plant. Leaf breadth, pedicel length of male flower, number of male flowers/plant and fruits/plant were the important components of genetic divergence in the studied materials. Based on inter cluster distance, inter genotypic distance and consideration of desirable characters for high yield potential, the genotypes G19 (BARI mistikumra-1) and G20 (BARI mistikumra-2) from cluster II; G21 (BD-2150) from cluster I and G1 (BD-2151) and G13 (BD-266) from cluster III can be selected as better parents for future hybridization program.Bangladesh J. Agril. Res. 40(4): 683-692, December 2015